A semi-heterarchical production control architecture for industry 4.0-based manufacturing systems. (April 2020) - Grassi, Andrea; Guizzi, Guido; Santillo, Liberatina Carmela; Vespoli, Silvestro
Abstract: The paper presents a novel architecture for production planning and control characterized by a semi-heterarchical structure in which different management levels are identified by both their physical identity and functional scope. The architecture is developed in three management levels: the Knowledge-based Enterprise Resource Planning (the business level, also accountable for cloud interaction); the High-Level Controller (the general performance level); the Low-Level Controller (the operative level). The proposed architecture represents an enhanced implementation of the Industry 4.0 decentralized decision concept, enabling a better knowledge and control of system performances to deliver increased profit and response time predictability in highly customised scenarios.